Expect the Unexpected—First Case of Congenital Rubella Syndrome in Israel in 20 Years: A Case Report. (26th July 2021) - Molad, Michal; Gover, Ayala; Ephros, Moshe; Lavie-Nevo, Karen; Waisman, Dan; Levin, Tal; Kanaaneh, Yara; Indenbaum, Victoria
Abstract: Congenital rubella syndrome (CRS) is a devastating condition associated with significant morbidity. Due to universal vaccination programs, it is currently a rare condition, especially in developed countries. We report an infant born in Israel to a foreign worker from the Philippines who presented with a blueberry muffin rash immediately after birth. Initial workup revealed sonographic brain anomalies, abnormal hearing tests, and a patent ductus arteriosus. CRS was subsequently confirmed by laboratory diagnosis. Rubella virus genotype 1E was detected in the infant's nasopharyngeal swab and urine samples. This was the first case of CRS in Israel in 20 years, emphasizing the need to "think outside the box" when dealing with infants of mothers who are foreign workers, refugees, or visitors of foreign relatives, in which rubella immune status is unknown. Additionally, public health authorities should consider the routine assessment of rubella immunity status of foreign workers in order to avoid such tragic, preventable diseases. We present a case of congenital rubella syndrome – rarely seen in developed countries. This emphasis the need to "think out of the box" when dealing with infants of mothers who come from countries in which the vaccination program is not well established.